External Validation of Three Burn-Specific Mortality Prediction Models in Adult Burn Patients at a Tertiary Care Hospital in India - Sneha Sharma; Raman Tandon (Indian Journal of Plastic Surgery, 2023)
Background Several burn-specific mortality prediction models have been formulated and validated in the developed countries. There is a dearth of studies validating these models in the Indian population. Our objective was to validate three such models in the Indian burn patients. Methods A prospective observational study was performed after ethical clearance on consecutive eligible consenting burn patients. Patient demographics, vitals, and results of hematological workup were collected. Using these. the Abbreviated Burn Severity Index (ABSI), the revised Baux score (rBaux), and the Fatality by Longevity, APACHE II score, Measured extent of burn, and Sex score (FLAMES) were calculated. The discriminative ability of the ABSI, rBaux, and the FLAMES was tested using the receiver operating characteristic (ROC) curve at 30 days and the area under the ROC curve (AUROC) compared. A p-value ≤ 0.05 was considered significant. Probability of death was calculated using these models. Hosmer–Lemeshow goodness of fit test was run. Results The ABSI (AUROC 0.7497, 95% CI 0.67796–0.82141), rBaux (AUROC 0.7456, 95% CI 0.67059–0.82068) and FLAMES (AUROC 0.7119, 95% CI 0.63209–0.79172), had fair discriminative ability. The Hosmer–Lemeshow test reported that ABSI and rBaux were a good fit for the Indian population, while FLAMES was not a good fit. Conclusion The ABSI and rBaux had a fair discriminative ability and were a good fit for the adult patients with 30 to 60% thermal and scald burn patients. FLAMES despite having fair discriminative ability was not a good fit for the study population.